Tuberculids: A narrative review - Niharika Dhattarwal; V Ramesh (Wolters Kluwer Medknow Publications, 2023)
Tuberculids are a group of dermatoses with tuberculoid histology and the absence of tubercle bacilli. They are considered to be hypersensitivity reactions to circulating Mycobacterium tuberculosis (M. tb) or its antigens in individuals with good immunity. The objective of the review is to provide a detailed literature review of all available articles on tuberculids in the past 10 years and provide an update on epidemiology, etiopathogenetic mechanisms, clinical manifestations, and treatment. A search was performed on PubMed using the keywords lichen scrofulosorum, papulonecrotic tuberculid, erythema induratum, and erythema nodosum tuberculosis for all articles, with no restrictions on age, gender, or nationalities. An update on tuberculids, including some new concepts in pathogenesis, atypical presentations, new investigative modalities, and treatments are reviewed.